HUMAN RIGHTS IN PERSPECTIVE: HISTORY, SOCIAL POLITICS AND INTERSETORIALITY - Martins Ramos Rodrigues, Victor; Garcia Pinho, Leandro (LINKSCIENCEPLACE, 2026)
The issue of human rights has become a feature on social agendas for a long time. However, the complexity and breadth of human rights necessarily mean that we must constantly revise the theme, integrating it with the existing discussions of the new approaches and demands that are presented daily in this already troubled era. From this, the proposal of this article is to resume an analysis of broader aspects that can contribute to the understanding of the human rights issue in its historical aspects and its insertion as social rights. From this starting point, the idea is to revisit the notions of social policies and their relationship with social rights and, secondly, to rethink human rights from the notion of intersectoriality. To this end, the methodological proposal, with a qualitative character, presupposes a re-reading of the classical and historical approaches of the theme, as well as a collection of recent discussions on the theme. It starts with regulatory, documentary and bibliographic sources to bring up a topic of extreme importance for the present day, but still full of possibilities for analysis.